(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Electrical resistivity tomography is a geophysical method that was used to characterize the soil in Ahamdu Bello University Phase II, Zaria. Ahmadu Bello University site II lies between longitudes 7° 37.98’ E and 7° 39.07’ E and latitudes 11° 7.86’ N and 11° 8.50’ N. A multi-electrode resistivity meter (ABEM Terrameter SAS 4000) was used for data acquisition on the field using a dipole-dipole array and the data were processed and interpreted using RES2DINV. The results obtained from the resistivity tomograms of the three profiles were used to correlate with the borehole data and the correlation indicates four distinct layers (Topsoil, weathered basement, fractured and fresh basement). The most competent layer for building a foundation in the study area is the fresh basement which is about 15.9m deep from the earth surface. In this study, electrical resistivity tomography has been successfully used to determine the depth to basement and the extent to which the bedrock was delineated. Weak zones that may be prone to subsidence and the competent areas that can support massive engineering were identified